The dense medium cyclone – past, present and future. (15th January 2018) - Napier-Munn, Tim
Highlights: The dense medium cyclone is a mature and efficient process. The behaviour of the medium is process-determining. Semi-empirical models exist which can be used for process design and optimisation. Economics will be greatly improved with larger cyclones and lower heads, as in coal preparation. The DMC can compete effectively as a process of choice for the pre-concentration of mineral ores. Abstract: Since the dense medium cyclone (DMC) was first patented in the 1940s it has become the process of choice in coal preparation, and is also widely used for upgrading iron ore and in the pre-concentration of diamonds and metalliferous and industrial minerals. It is in every sense a mature technology. This paper summarises the history of the process, considers its current status in mineral and coal processing, and suggests ways in which the process might evolve. Aspects reviewed include the process principles, process models, the importance of medium behaviour, particle size limitations, process analysis, instrumentation and control, and increases in scale. Particular attention is given to the potential for the use of larger cyclones at lower heads in mineral separations, as practiced in the coal industry. Using operating examples and published modelling results, the paper makes the case that these conditions will work in minerals too, and should be adopted. This will significantly improve the economics of DMC mineral separations at a time when pre-concentration is becoming more important for upgrading lower grade ores.